Electrochemical Aptasensing for Lifestyle and Chronic Disease Management - Upasham, Sayali; Pali, Madhavi; Jagannath, Badrinath; Lin, Kai-Chun; Prasad, Shalini (Current Medicinal Chemistry, 2023)
Over the past decade, researchers have investigated electrochemical sensing for the purpose of fabricating wearable point-of-use platforms. These wearable platforms have the ability to non-invasively track biomarkers that are clinically relevant and provide a comprehensive evaluation of the user’s health. Due to many significant operational advantages, aptamer-based sensing is gaining traction.Aptamer-based sensors have properties like long-term stability, resistance to denaturation, and high sensitivity. Using electrochemical sensing with aptamer-based biorecognition is advantageous because it provides significant benefits like lower detection limits, a wider range of operations, and, most importantly, the ability to detect using a label-free approach. This paper provides an outlook into the current state of electrochemical aptasensing. This review looks into the significance of the detection of biomarkers like glucose, cortisol etc., for the purpose of lifestyle and chronic disease monitoring. Moreover, this review will also provide a comprehensive evaluation of the current challenges and prospects in this field.
Keywords: biomarker